Persistent viral RNA shedding after COVID‐19 symptom resolution in older convalescent plasma donors. Issue 10 (24th June 2020) - Hartman, William R.; Hess, Aaron S.; Connor, Joseph P.
Abstract: Introduction: The novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is responsible for a worldwide pandemic. While the medical community understands the mode of viral transmission, less is known about how long viral shedding occurs once viral symptoms have resolved. Our objective was to determine how long the SARS‐CoV‐2 remains detectable following self‐reporting of viral symptom resolution. Methods: This study was approved by the University of Wisconsin Institutional Review Board. A cohort of patients who were previously SARS‐CoV‐2 positive less than 28 days after self‐reported symptom resolution were retested for proof of viral recovery by nasal swab reverse transcriptase polymerase chain reaction for SARS‐CoV‐2 RNA. Results: A total of 152 potential participants were screened, of which 5 declined, 54 were ineligible, and 93 were recruited; 86 of 93 completed testing. Eleven of 86 (13%) were still positive at a median of 19 days (range, 12‐24 days) after symptom resolution. Positive participants were significantly older than negative participants (mean, 54 years; 95% confidence interval [CI], 44‐63 vs 42 years; 95% CI, 38‐46; P = .024). C T values were significantly, inversely associated with age (β = −.04; r 2 = 0.389; P = .04). The number of days since symptom recovery was not apparently different between positive and negative participants. Conclusion: We found evidence of persistent viral shedding in nasopharyngeal secretions more than 2 weeks after resolution of symptoms from confirmed COVID‐19 infection. Persistent shedding was more common in older participants, and viral load was higher among older positive participants. These results underscore the necessity of testing COVID‐19 convalescent plasma donors less than 28 days after symptom resolution.